Polymer-based antimicrobial strategies for periodontitis - Chen, Jiajia; Dong, Shujun (Frontiers in Pharmacology, 2025)
Periodontitis is a chronic inflammatory condition driven by plaque-associated microorganisms, where uncontrolled bacterial invasion and proliferation impair host immune responses, leading to localized periodontal tissue inflammation and bone destruction. Conventional periodontal therapies face challenges, including incomplete microbial clearance and the rise of antibiotic resistance, limiting their precision and effectiveness in managing periodontitis. Recently, nanotherapies based on polymeric materials have introduced advanced approaches to periodontal antimicrobial therapy through diverse antimicrobial mechanisms. This review explored specific mechanisms, emphasizing the design of polymer-based agents that employ individual or synergistic antimicrobial actions, and evaluated the innovations and limitations of current strategies while forecasting future trends in antimicrobial development for periodontitis.